2019
DOI: 10.1002/pmic.201800421
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Oxidative Modifications and Impairment of Specific Metabolic Pathways During Cellular Senescence and Aging

Abstract: Accumulation of oxidatively modified proteins is a hallmark of organismal aging in vivo and of cellular replicative senescence in vitro. Failure of protein maintenance is a major contributor to the age‐associated accumulation of damaged proteins that is believed to participate to the age‐related decline in cellular function. In this context, quantitative proteomics approaches, including 2‐D gel electrophoresis (2‐DE)‐based methods, represent powerful tools for monitoring the extent of protein oxidative modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…After years of research, researchers have put forward many hypotheses about aging mechanism, such as oxidative stress, genetic determination theory, free radical theory, neuroendocrine theory, mitochondrial damage theory, etc. [4,6,7]. Most importantly, increasing oxidative stress, a major characteristic of aging, has been implicated in various age-related diseases [8].…”
Section: Introductionmentioning
confidence: 99%
“…After years of research, researchers have put forward many hypotheses about aging mechanism, such as oxidative stress, genetic determination theory, free radical theory, neuroendocrine theory, mitochondrial damage theory, etc. [4,6,7]. Most importantly, increasing oxidative stress, a major characteristic of aging, has been implicated in various age-related diseases [8].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the irreversible oxidative modifications of proteins are becoming more and more prominent in key cellular pathways and the pathogenesis of age-related diseases [151,152].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the complexity in redox‐mediated signaling pathways involved in senescence, redox proteomics would be the ideal approach to identify redox modified proteins. Interestingly supporting the role for oxidants in the regulation of signaling pathways during the establishment of senescence, it was shown that proteins targeted for oxidative modification in human fibroblasts undergoing replicative senescence fall into three main categories: energy metabolism, quality control‐stress response, and cytoskeleton organization . Similarly, data obtained through comparison of brain regions from senescent rats (28 months) with adult rats (12 months) by redox proteomics have identified oxidatively modified proteins that are involved in energy metabolism, cell structure, signal transduction, and the cellular stress response .…”
Section: Proteomic and Oxidants And Senescencementioning
confidence: 93%
“…Interestingly supporting the role for oxidants in the regulation of signaling pathways during the establishment of senescence, it was shown that proteins targeted for oxidative modification in human fibroblasts undergoing replicative senescence fall into three main categories: energy metabolism, quality control-stress response, and cytoskeleton organization. [142] Similarly, data obtained through comparison of brain regions from senescent rats (28 months) with adult rats (12 months) by redox proteomics have identified oxidatively modified proteins that are involved in energy metabolism, cell structure, signal transduction, and the cellular stress response. [143] More recently, a study on adipocyte mitochondrial proteome has unveiled increased Cysteine oxidation and decreased protein abundance in aging and Type II diabetes conditions.…”
Section: Proteomic and Oxidants And Senescencementioning
confidence: 99%